TECHNOLOGICAL ROADMAP OF COFFEE PROCESSING AND APPLICATIONS - Pimentel, Uilla (2024)
Coffee is one of the most consumed beverages in the world. Consumers of this beverage are looking for quality products and services. Therefore, coffee processing has been improving. In order to understand the technologies related to the processing of coffee beans and their applications, a Technological Map of Coffee was prepared. Initially, companies that operate in the coffee trade (beans, powder, capsules and soluble) and companies that sell processing equipment were verified. According to short and medium-term information, it was possible to indicate that large companies in the coffee sector dominate the market for capsules. Another piece of information found was the tendency to use coffee for human health, such as weight loss (green coffee) and its antioxidant activity. Finally, several articles in the area of ​​reuse were found, advocating interest in the life cycle of products and their versatility